Activity limitations in leprosy and their association to cognition and neuropsychiatric symptoms - Luana Karen dos Santos Amaral; Lilian Assunção Felippe; Gláucia Helena Gonçalves; Gustavo Christofoletti
ABSTRACT Objectives: to analyze activity limitations in patients with leprosy and their association to cognition and neuropsychiatric symptoms. Methods: this cross-sectional design study included sixty patients with multibacillary leprosy assisted at a reference center. Participants were divided according to their physical disability and submitted to instruments assessing daily activities (basic and instrumental), cognitive functions, and neuropsychiatric symptoms. The order of the instruments was random to avoid any interference of test sequence on the results. Results: fifty-five percent of the participants presented physical disabilities. All patients were independent in performing basic activities but sixty-six percent presented difficulties in performing instrumental activities. Cognitive decline and neuropsychiatric symptoms were seen in advanced stages of the disease, but they were more associated to patient age than to leprosy. Conclusions: leprosy patients presented physical disabilities and difficulties in performing instrumental daily activities. Cognitive decline and neuropsychiatric symptoms were more associated to aging than to leprosy itself.